The association between the triglyceride–glucose index and prognosis in postoperative renal cell carcinoma patients: a retrospective cohort study - Qin, Guoliang; Sun, Zhuang; Jin, Yuxiang; Ren, Xiangguo; Zhang, Zhaocun; Wang, Shuo; Zhou, Guanwen; Huang, Kun; Zhao, Haifeng; Jiang, Xianzhou (Frontiers in Endocrinology, 2024)
Background Insulin resistance has been proven to be associated with renal cell carcinoma (RCC). However, the prognostic value of the triglyceride–glucose (TyG) index, as a marker for insulin resistance (IR), is still unclear. Therefore, we conducted research to explore the prognostic value and the predictive performance of the TyG index in postoperative RCC patients. Methods A total of 651 postoperative RCC patients from January 2016 to June 2018 were enrolled in the final study. Their clinical and laboratory parameters were collected from medical records and through follow-up by phone. The triglyceride–glucose (TyG) index was calculated as follows: TyG = Ln[TG (mg/dl) × FBG (mg/dL)/2]. The overall survival (OS) and disease-free survival (DFS) were identified as the main outcomes. Results The TyG index is an independent prognostic factor for OS (HR = 2.340, 95% CI = 1.506 to 3.64, P < 0.001) and DFS (HR = 2.027, 95% CI = 1.347 to 3.051, P < 0.001) in postoperative RCC patients. Kaplan–Meier survival curves of the different TyG index levels showed statistically significant differences in terms of OS and DFS (log-rank test, P < 0.0001). Furthermore, the TyG index was significantly associated with RCC risk factors. Conclusion The TyG index is significantly associated with RCC survival. The mechanisms responsible for these results may contribute toward the improvement of RCC prognosis and immunotherapy efficacy and the development of new immunotherapeutic targets.